Eingesperrt und abgehängt? Gefangenentelefonie im Lichte des Resozialisierungsanspruchs, des rechtlichen Rahmens und der Praxis im Ländervergleich - Kilchling, Michael (Kölner Schriften zur Kriminologie und Kriminalpolitik, 2022)
Access to telephone and other forms of electronic communication is one of the areas in which prison conditions vary significantly in Germany. The divergent conditions raise several fundamental human rights concerns, such as equal treatment of inmates, the right of resocialization, and the rights to privacy and family life. This volume provides a theoretical and empirically substantiated analysis of the impact and significance of telephone communication for resocialization and recidivism. German practices were also examined in light of the Council of Europe's standards for inmates' contacts with the outside world. An overview of key observations from the CPT's country reports regarding telephone communication of prisoners completes the book.